VITAMIN D SUPPLEMENTATION IN BREASTFEEDING WOMEN AND VITAMIN D STATUS IN INFANTS – A REVIEW OF CURRENT CLINICAL STUDIES - Judzińska, Alicja; Dubaj, Magdalena; Ignarska, Justyna; Kubicz Mzabi, Sabina; Kwolek, Marlena; Osipowska, Julia; Piech, Bartosz; Sobczyńska, Kamila; Terbosh, Magda; Trojanowska, Emilia (International Journal of Innovative Technologies in Social Science, 2026)
Background: Vitamin D deficiency is a major public health concern, particularly among breastfed infants, whose vitamin D status depends largely on maternal 25-hydroxyvitamin D [25(OH)D] levels during pregnancy and lactation. Maternal supplementation has been proposed as a strategy to improve infant vitamin D status.Objective: This review aimed to evaluate the effect of vitamin D supplementation in breastfeeding women on 25(OH)D concentrations in exclusively breastfed infants.Materials and Methods: A narrative review of randomized controlled trials published between 2015 and 2025 was conducted. Ten studies assessing maternal vitamin D supplementation and its impact on infant 25(OH)D levels were included.Results: Maternal supplementation increased 25(OH)D levels in both mothers and infants. However, standard doses (400–800 IU/day) were often insufficient to achieve adequate vitamin D status in infants. Higher doses, particularly ≥4000 IU/day, resulted in significant improvements and, in some cases, achieved levels comparable to direct infant supplementation.Conclusions: Vitamin D supplementation in breastfeeding women may effectively improve infant vitamin D status, especially at higher doses. However, its efficacy depends on dosage, and further research is needed to determine optimal and safe supplementation strategies.